Chemical Properties, Biological Activities and Poisoning Treatment of Novichok: A Review - Rahmania, Tesia Aisyah; Wardhani, Bantari Wisynu Kusuma; Renesteen, Editha; Harahap, Yahdiana (Pharmaceutical Sciences and Research, 2021)
Novichok is an organophosphate compound found as a nerve agent chemical weapon. However, the information about its chemical properties, biological activities, and molecular interactions in the body are still protected under the “top secret” security clearance. Novichok, with the codes A230, A232 and A234, is a compound whose structure has been successfully determined. The compound is synthesized from a precursor through a nucleophilic substitution reaction. Novichok agents are considered more potent than VX gas and can be applied in unitary and binary forms. This compound has ability for the binding with acetylcholinesterase (AChE) due to inability of acetylcholine metabolism. AChE catalyzes the rapid hydrolysis of acetylcholine to acetate and choline. The treatment of Novichok agent poisoning is similar to management of other nerve agents, such as atropine and pralidoxime administered intravenously. In this paper, we reviewed the Novichok component from chemical and biological perspective. Moreover, we discussed the potential molecular interaction and treatment of this compound.